Antioxidant effect of carnosine treatment on renal oxidative stress in streptozotocin-induced diabetic rats. (November 2014) - Yay, A; Akkuş, D; Yapıslar, H; Balcıoglu, E; Sonmez, MF; Ozdamar, S
Abstract: Nitric oxide (NO) plays a significant role in the development of diabetic nephropathy. We investigated the effects of an antioxidant, carnosine, on streptozotocin (STZ)-induced renal injury in diabetic rats. We used four groups of eight rats: group 1, control; group 2, carnosine treated; group 3, untreated diabetic; group 4, carnosine treated diabetic. Kidneys were removed and processed, and sections were stained with periodic acid-Schiff (PAS) and subjected to eNOS immunohistochemistry. Examination by light microscopy revealed degenerated glomeruli, thickened basement membrane and glycogen accumulation in the tubules of diabetic kidneys. Carnosine treatment prevented the renal morphological damage caused by diabetes. Moreover, administration of carnosine decreased somewhat the oxidative damage of diabetic nephropathy. Appropriate doses of carnosine might be a useful therapeutic option to reduce oxidative stress and associated renal injury in diabetes mellitus.